Carbon forestry: who will benefit?: proceedings of Workshop on Carbon Sequestration and Sustainable Livelihoods, held in Bogor on 16-17 February 2005 - Murdiyarso, Daniel; Herawati, H. (Center for International Forestry Research, 2005)
Carbon sequestration projects through land use, land-use change and forestry (LULUCF) activities could demonstrate a win-win situation from the point of view of climate change and sustainable development. Under the current rules of the Clean Development Mechanism (CDM) of the Kyoto Protocol the activities are limited to afforestation and reforestation. Properly designed, these projects conserve and/or increase carbon stock and at the same time improve rural livelihoods. Such projects have been developed and implemented in a number of countries with different ecosystems and social settings. They do not necessarily comply with the current legally binding carbon market under CDM but demonstrate the participation of the low-income rural communities in sustainable forestry, agroforestry and other natural resource management activities.This publication is a collection of the lessons learned from a number of case studies ranging from small to large scale projects, from community-based to corporate operations, and from development to conservation activities. Although most projects are still in their infancy stage and many more lessons to be learned it was realized that bundling climate change and community development projects is a practical approach to support sustainable livelihoods. At the same time the strategic approaches to influence the next rounds of climate negotiation were also addressed. These are dealing with issues, such as, avoiding deforestation and adaptation measures for vulnerable ecosystems and communities, who have relatively low adaptive capacity. Emerging markets for carbon in the context of rural development and organization were identified. This transition has had implications for the development of its institutional arrangements at project management and community levels, which in turn have affected the project’s legitimacy and its ability to promote equitable outcomes. It has been demonstrated that purely carbon management-oriented activities are able to convince rural communities and investors to participate. Broader carbon forestry activities have the potentials to be integrated in the sustainable development agenda.